MATHEMATICS, PHYSICS AND THE REAL FACE OF GOD. - Aldworth, Roland (Contemporary Review, 2001)
Focuses on the concepts of mathematics and science, and its role in proving the reality of objects and human existence. Obstacles to the development of a theory to explain the realities of everything; Details on several theories of realities.